2017
DOI: 10.3201/eid2307.151251
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors as Key Determinants for Visceral Leishmaniasis in Solid Organ Transplant Recipients, Madrid, Spain

Abstract: During a visceral leishmaniasis outbreak in an area of Madrid, Spain, the incidence of disease among solid organ transplant recipients was 10.3% (7/68). Being a black person from sub-Saharan Africa, undergoing transplantation during the outbreak, and residing <1,000 m from the epidemic focus were risk factors for posttransplant visceral leishmaniasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…The recent outbreak of leishmaniasis in Fuenlabrada (southwest Madrid, Spain), with a mean incidence rate of 22.2 per 100,000 inhabitants in the general population [ 32 ], has allowed the study of a cohort of patients with SOT living in the area [ 33 ]. During the outbreak, a total of 7 VL cases were counted amongst the 68 SOT recipients included in the study, yielding an annual incidence of 2,997 cases per 100,000 population.…”
Section: Resultsmentioning
confidence: 99%
“…The recent outbreak of leishmaniasis in Fuenlabrada (southwest Madrid, Spain), with a mean incidence rate of 22.2 per 100,000 inhabitants in the general population [ 32 ], has allowed the study of a cohort of patients with SOT living in the area [ 33 ]. During the outbreak, a total of 7 VL cases were counted amongst the 68 SOT recipients included in the study, yielding an annual incidence of 2,997 cases per 100,000 population.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the major risk factor for VL appears to be related to the prevalence of the disease, as suggested by two studies involving SOT patients from endemic areas [16,66]. Additionally, in a recent outbreak of leishmaniasis in Spain, the risk of developing VL was 135 times higher in SOT patients than in immunocompetent individuals from the same area [18]. Regarding the immunosuppression (IS) regimen, the risk of VL increases with the use of high-dose steroids [16].…”
Section: Risk For the Recipient: Infection And Reactivationmentioning
confidence: 99%
“…Interestingly, a study conducted in Madrid during an outbreak of leishmaniasis found an annual risk of developing VL among SOT recipients 136 times higher compared to immunocompetent subjects living in the same area [80]. Three risk factors emerged as associated with the diagnosis of VL: 1) living in close proximity to the area affected by the outbreak (relative risk 11.74%), explained by a higher chance to be bitten by the infected phlebotomous; 2) receiving a SOT during the outbreak; and 3) being black from sub-Saharan Africa, with a relative risk of 6.40% [80]. The role of ethnicity and its possible association with VL needs to be explored in future studies, as black people emerged as the most affected in another study from Brazil [81].…”
Section: Risk Factorsmentioning
confidence: 99%
“…VL is by far the most frequently encountered clinical presentation of leishmaniasis among SOT recipients described in kidney, liver, heart, lung, and pancreas transplantation [7,68,[79][80][81]. Fever is the most common symptom of VL, but in the study by Clemente et al, 14% of patients were afebrile [68,79].…”
Section: Clinical Presentationmentioning
confidence: 99%